Developing 21st-Century Skills Through Robotics-Enhanced STEM Learning: Effects on Prospective Elementary Teachers’ Computational Thinking - Fitri Nuraeni; Nenden Permas Hikmatunisa; Endah Setyowati; Hafiziani Eka Putri; Afridha Laily Alindra (Phenomenon : Jurnal Pendidikan MIPA, 2025)
Currently the integration of Computational Thinking (CT) has been promoted into learning since elementary school due to technology advancement. However, prospective elementary school teachers in Indonesia lack sufficient experience in implementing CT into practice, leading to unpreparedness in teaching these skills to students in the future. STEM Education course provide a strategic platform to equip prospective elementary school teachers with hands-on experience in developing CT. Robotics integration enable combination of science, technology, engineering, and mathematics in one unit, and also provides project-based problem-solving experiences that can enhance CT. Through a quasi-experimental design, this study explore the effectiveness of robotics integration in STEM Education course in improving prospective elementary school teachers' CT. A total of 95 prospective elementary teachers comprised the study sample, which was selected purposively. The Computational Thinking Scale, with twenty-two items, was tested and found to be valid and reliable. Mixed ANOVA analysis indicates that STEM-based robotics course had a significant effect on improving elements of CT that includes problem-solving and critical thinking indicators. Meanwhile, the treatment effects on creativity, algorithmic thinking, and cooperativeness were minimal, indicating that these three indicators did not significantly influenced by the intervention